Students’ Perception on the Effect of YouTube Livestream to Their Receptive Skills and English Component - M. Nasrullah Amamy (Journal of English Language and Education, 2026)
The increasing popularity of YouTube livestreams as a form of digital media has generated growing interest in their potential contribution to English language learning. This study explores university students’ perceptions of the impact of YouTube livestreams on the development of receptive English skills and language components. A qualitative approach was employed through semi-structured interviews with two university students who regularly engaged with English-language livestream content. The interview data were analyzed using thematic analysis to identify recurring patterns and perceptions. The findings indicate that participants perceived noticeable improvements in listening comprehension, vocabulary acquisition, and pronunciation awareness through repeated exposure to authentic spoken English. However, both participants reported limited benefits for reading skills and expressed uncertainty regarding the influence of livestreams on grammar development, suggesting that these aspects require more explicit instructional support. Overall, the findings suggest that YouTube livestreams can serve as a valuable supplementary resource for developing receptive language skills, particularly listening and vocabulary. Nevertheless, the study is limited by its small and relatively homogeneous sample and its reliance on self-reported perceptions rather than objective measures of language proficiency. Future research involving larger and more diverse participant groups is recommended to validate and extend these findings.